Literature Review Peran Perawat Dalam Upaya Kesehatan Masyarakat (UKM) di Puskesmas - Karina, Cindy; Sabrian, Febriana; Agrina (Jurnal Keperawatan Muhammadiyah, 2025)
Introduction: : Nurses play an important role in the implementation of public healthefforts (PHEs) because they are directly involved in the delivery of health services tothe community. However, research in research related to the overall role of nurses inimplementing PHEs is still limited and requires further exploration, so a literaturereview was conducted to look at the overall role of nurses and present existing evidencebased and show gaps related to the role of nurses in the implementation of PHEs inPrimary health care. Objective: This literature review aims to identify the rolesperformed by nurses and see the involvement in implementing PHEs comprehensivelythrough the results of research that has been done. Methods: This literature review wascarried out with a search strategy stage by applying keywords and screening adjusted tothe inclusion and exclusion criteria, then the results of data extraction were presented inthe form of a PRISMA scheme. Results: The results of a search of 27 articles showedthat nurses have diverse roles in the implementation of PHEs in Primary health care,namely as educators, case finders, care giver, collaborators, coordinators, counselors,and role models. However, the most dominant role implemented is the role as aneducator. The results of the article identification also show that nurses contribute moreto PHEs, namely health promotion efforts. Conclusion: Nurses are mostly involved andcarry out the role of educator but the role of nurses as counselors and role models needsto be studied more deeply. Also, it is necessary to conduct a deeper study related to PHEssuch as complementary health efforts which are part of a holistic approach in improvingpublic health status.Keywords: Role of nurses, public health efforts (EPH), Primary Health CareReferences: 66 (2006-2025)